The Effectiveness of Accounting Information Systems on Vehicle Sales Growth - Salam, Rendy (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2022)
To get big profits, companies must have a good management system, namely how the business is managed professionally, one of which is having a sales accounting information system. This system helps companies record all transactions, thereby generating information that helps companies monitor business progress. This research was conducted on the basis of qualitative methods with descriptive analysis techniques. This research was conducted at PT. Istana Kebon Jeruk by analyzing data flow diagrams and internal control questionnaire techniques. The results show that the accounting system provides an actual picture of all business processes, thereby reducing various risks of loss. In addition, the accounting system provides information about sales and revenue trends, thereby helping operations managers make informed decisions.